Imaging Spectroscopy: Earth and Planetary Remote Sensing with the PSI Tetracorder and Expert Systems from Rovers to EMIT and Beyond - Roger N. Clark; Gregg A. Swayze; K. Eric Livo; Philip G. Brodrick; Eldar Noe Dobrea; Srinivasan Vijayarangan; Robert O. Green; David Wettergreen; Alberto Candela; Amanda Hendrix; Carlos Pérez García-Pando; Neil C. Pearson; et al. (The Planetary Science Journal)
A system for rapid analysis of spectroscopy data with emphasis on planetary surfaces, both imaging and single-spectrum data, is described. The system, called Tetracorder, is commanded by an expert system developed by expert spectroscopists. The Tetracorder and the expert system apply multiple algorithms to analyze a spectrum in segments, leveraging the advantages of each spectral region’s sensitivity to detecting different compounds, whether solid, liquid, or gas. The algorithms compare measured spectra to the spectral properties of materials in spectral libraries. The libraries include pure minerals, mineral mixtures that include areal mixtures, intimate mixtures, coatings, and molecular mixtures and other compounds such as organics, vegetation, liquids, and gases. Absorption bands of a particulate surface change shape with grain size, and shape changes are used in some cases to constrain grain size of each component in the surface. The different algorithm results are compared for each spectral region, and specific material composition and average grain size (when possible) are identified. The system is operational analyzing real-time data on a new generation of rovers for future planetary missions, as well as identifying materials using an imaging spectrometer on the International Space Station. Four abundance models are presented, each with increasing sophistication, that are computationally fast on imaging spectrometer data and use Tetracorder identifications to produce maps of mineral abundances. A fifth full radiative model that includes multilayer surfaces is presented but is computationally intensive. The system is open source and available on GitHub.